Parathyroid Hormone-Like Hormone is a Poor Prognosis Marker of Head and Neck Cancer and Promotes Cell Growth via RUNX2 Regulation - Chang, Wei-Min; Lin, Yuan-Feng; Su, Chia-Yi; Peng, Hsuan-Yu; Chang, Yu-Chan; Hsiao, Jenn-Ren; Chen, Chi-Long; Chang, Jang-Yang; Shieh, Yi-Shing; Hsiao, Michael; Shiah, Shine-Gwo (Scientific reports, 2017)
Parathyroid Hormone-Like Hormone (PTHLH) is an autocrine/paracrine ligand that is up-regulated in head and neck squamous cell carcinoma (HNSCC). However, the cellular function and regulatory mechanism in HNSCC remains obscure. We investigated the clinical significance of PTHLH in HNSCC patients, and verified the role of RUNX2/PTHLH axis, which is stimulated HNSCC cell growth. In patients, PTHLH is a poor prognosis marker. PTHLH expression lead to increasing the cell proliferation potential through an autocrine/paracrine role and elevating blood calcium level in Nod-SCID mice. In public HNSCC microarray cohorts, PTHLH is found to be co-expressed with RUNX2. Physiologically, PTHLH is regulated by RUNX2 and also acting as key calcium regulator. However, elevations of calcium concentration also increased the RUNX2 expression. PTHLH, calcium, and RUNX2 form a positive feedback loop in HNSCC. Furthermore, ectopic RUNX2 expression also increased PTHLH expression and promoted proliferation potential through PTHLH expression. Using cDNA microarray analysis, we found PTHLH also stimulated expression of cell cycle regulators, namely CCNA2, CCNE2, and CDC25A in HNSCC cells, and these genes are also up-regulated in HNSCC patients. In summary, our results reveal that PTHLH expression is a poor prognosis marker in HNSCC patients, and RUNX2-PTHLH axis contributes to HNSCC tumor growth.